A Literature Review: Active Compound Content and Pharmacological Activity of Bitter Melon Plant (Momordica charantia L.) for Health - Virdausy, Venya Nabila; Sabrina, Faizah Erica Andi; Jannah, Akyunul (Jurnal Biologi Tropis, 2025)
Bitter melon (Momordica charantia L.) is a climbing plant that has benefits for the community's medicinal system. This review article aims to explore the active compound content and pharmacological activity of the M. charantia plant in the health sector. This study employed a literature review method by gathering data from various references, including journals, books, online articles, and other forms of literature, and summarizing the findings. The bioactive compounds of this plant are triterpenoids, steroids, flavonoids, tannins, saponins, alkaloids, polyphenols and glycosides. The bioactive content in the M. charantia plant can be used in the health sector, such as antidiabetic, antibacterial, antioxidant and anticancer. Its traditional uses and modern scientific research highlight its potential as an exploitable resource. The biological effects of M. charantia extract have a direct impact on human health. The results of this review are valuable as they can guide future research on the extraction of bioactive compounds from M. charantia and their potential applications.